Clonal micropropagation of Pistacia lentiscus L. and assessment of genetic stability using IRAP markers - ALTINKUT UNCUOĞLU, AHU (SPRINGER, 2015)
An efficient protocol for clonal micropropagation of selected genotypes of lentisk, Pistacia lentiscus L., which is cultivated for the masticha resin, has been developed using shoot tip explants originating from in vitro seedlings. BA was found to be optimum for shoot morphogenesis in terms of the number and length of shoots among the cytokinins tested for all cloned genotypes, while the highest shoot length was noticed in the presence of 2iP at a rate 4.92 mu M. Efficient rooting (94.15 %) was achieved in a medium containing 19.6 mu M IBA with the clone II that was superior to the rest of the clones tested. The method developed for plant acclimatization was satisfactory because a high percentage of plant survival (95 %) in the growth room in the clone II was obtained and the regenerated plantlets resumed growth after 4 months. DNAs from mother seedlings and micropropagated plantlets belonging to 6, 9 and 12 times subcultured were isolated and subjected to IRAP analysis in order to evaluate their genetic stability and detect possibly existing variations among in vitro derived plantlets. The mean percentage of similarity calculated by Jaccard's similarity coefficient ranged from 78 to 86 % in the four genotypes. Although variation was observed among mother plantlets and its regenerants for all of the clones, polymorphic information content value in the range of 0.391-0.405 indicated the presence of reasonable polymorphism within the clones. The presented data confirmed that the clonal propagation of lentisk by using shoot tips could be used for commercial exploitation of the selected genotype.
Keywords: Clonal micropropagation; Genetic fidelity; Lentisk; Mastic tree; PCR-based marker; SOMACLONAL VARIATION; SOMATIC EMBRYOGENESIS; CULTURES; RETROTRANSPOSONS; PROPAGATION; EXPLANTS; REMAP